Occurrence of borate mineralization and the relationship of chemical equilibrium between sodium calcium borates in the salt pan of Laguna Salinas in the district of San Juan de Tarucani – Arequipa - Ccama Cabana, César Augusto (2022)
In Peru there is the only boratifero deposit of the salar type, the Laguna Salinas, which is characterized by being formed under certain environmental factors of evaporitic origin, determined by endogenous and supergenic processes (endoreic system), now, we must understand how it was formed and what is its relationship in geological time with respect to its chemical equilibrium. In Lagunas Salinas, ulexite is extracted, which is a hydrated calcium and sodium borate, which we see that due to its characteristics it is possible to give a relationship on its occurrence over other similar borates and the reason for its dominance in the area over other boratiferous species. The objective of the research is to determine the mineralized horizons of ulexite in relation to the chemical equilibrium between the formation temperature and the water content that these boratiferous species present. The research is of the non-experimental type, that is, the samples that were taken in the field were analyzed to see the relationship between their formation temperature and the amount of water that they have among themselves, which was able to conclude sequential depositions schemes which give the opportunity to extract new borates and to learn more about this type of deposits.